Simulation of Vibro-Impact Systems Using Reciprocal Mass Matrices - Tkachuk, Anton; Bischoff, Manfred (NTU "KhPI", 2016)
Computation cost of explicit time integration can be reduced substantially using the reciprocal mass matrices. General variational derivation of the method, its verification by an eigenvalue benchmark and comparison on a transient example are presented in this contribution.
Keywords: reciprocal mass matrix; selective mass scaling; explicit dynamics